AKTIVITAS ANTIOKSIDAN PROTEIN HIDROLISAT DARI KASEIN SUSU KAMBING ETAWA HASIL HIDROLISIS BROMELIN DARI DAUN NANAS MADU - Puji Lestari; Suyata Suyata (Jurnal Gizi dan Pangan Soedirman, 2020)
Hydrolyzed proteins are fragments of protein fragments that have certain biological activities. Some of the functions of hydrolyzed proteins that are known are as antibacterial, antioxidant, antihypertensive, antithrombotic, anti-inflammatory, opioid, and immunomodulatory. Protein from Etawa goat's milk is one source of protein hydrolyzate. In this research, the antioxidant activity of protein hydrolyzate from casein Etawa goat milk was tested. Casein is hydrolyzed with bromelain from honey pineapple leaves. The research steps are: bromelain extraction, casein hydrolysis of Etawa goat milk, antioxidant activity fraction of hydrolyzed protein fractions by DPPH method, and hemolysis test. The results of the study were: (1) the highest degree of hydrolysis in casein hydrolyzate was achieved at 60 minutes incubation time, (2) casein hydrolyzate which had the highest antioxidant activity was incubated for 30 minutes, (3) based on the AAI value, the casein hydrolyzed activity included into the classification of weak antioxidants because AAI <0.5, (4) the results of the hemolysis test show that casein hydrolyzate does not cause hemolysis of red blood cells